2014
DOI: 10.1080/01402382.2014.911482
|View full text |Cite
|
Sign up to set email alerts
|

No Sex Scandals Please, We’re French: French Attitudes towards Politicians’ Public and Private Conduct

Abstract: Enlighten-Research publications by members of the University of Glasgow http://eprints.gla.ac.uk No sex scandals please, we're French: French attitudes towards politicians' public and private conduct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…On the other hand, we create three sets of vignettes differing in the scandal type (again using random assignment with equal probability): (1) an unspecified scandal without example or additional information (our baseline), (2) a financial scandal, and (3) a sex scandal. The choice of scandal types was driven by research indicating that financial and sex scandals are the most common types of scandals (Basinger 2012; Doherty, Dowling, and Miller 2011; Sarmiento‐Mirwaldt et al 2014). Random assignment of the resulting six vignettes allows us to assess the potential moderating roles of partisanship and scandal type on politicians’ preferred response strategies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, we create three sets of vignettes differing in the scandal type (again using random assignment with equal probability): (1) an unspecified scandal without example or additional information (our baseline), (2) a financial scandal, and (3) a sex scandal. The choice of scandal types was driven by research indicating that financial and sex scandals are the most common types of scandals (Basinger 2012; Doherty, Dowling, and Miller 2011; Sarmiento‐Mirwaldt et al 2014). Random assignment of the resulting six vignettes allows us to assess the potential moderating roles of partisanship and scandal type on politicians’ preferred response strategies.…”
Section: Methodsmentioning
confidence: 99%
“…The type of scandal is a second potential moderating factor for uninvolved politicians’ scandal response strategy. Two main scandal types are identified in the foregoing literature: that is, sex scandals (e.g., sexual misconduct or extramarital affairs) and financial scandals (e.g., tax evasion or accepting payment for political access) (Doherty, Dowling, and Miller 2011; Hamel and Miller 2019; Sarmiento‐Mirwaldt et al 2014). Importantly, voters perceive these two types of scandals very differently.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…a generic scandal (our ‘baseline’ treatment), a financial scandal, and a moral scandal. These scandal types are commonly differentiated in the literature (Sarmiento-Mirwaldt et al, 2014), and are most frequently observed in reality (Basinger, 2012). We introduce this variation in scandal types for two reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Much of the methodological controversy surrounding the measurement of corruption rests on the very notion of how one can create a generalisable definition of corruption (for a neat summary of definitional debates, see Hough, 2013: 2–5). In the European context, sex scandals are a good example – in France, politicians can remain relatively unpunished when they are caught in flagrante with someone ‘inappropriate’, whereas in Britain it can cause anything from huge embarrassment, to the end of a glittering career (Sarmiento-Mirwaldt et al, 2014). Therefore, we could easily conflate a discursive institutional strand with the historico-normative institutional understanding forwarded in the literature (Clift and Fisher, 2004, 2005; Fisher, 2009, 2011, 2015a).…”
Section: Party Funding Regime Change What We Knowmentioning
confidence: 99%